Serum vitamin D levels in high-risk HPV infected patients, is there any relation? - Anil Turhan Cakir; Muhammet Atay Ozten (National Scientific Medical Center, 2022)
Objective: Human Papilloma Virus (HPV) is a sexually transmittable virus and is the main etiologic cause of uterine cervical cancers. Beyond that, vitamin D is a steroid structured lipid-soluble vitamin, enhancing both humoral and cellular immune responses. In our study, we aimed to investigate the relationship between vitamin D levels and high-risk HPV infections. Material and methods: A total of 143 patients who applied to the gynecology outpatient clinic between June 2020 and August 2020 were included in the study. Patients with high-risk HPV positivity constituted the study group, and HPV-negative patients constituted the control group. Serum vitamin D levels were compared between the groups. Results: The mean vitamin D level of all patients included in the study, HPV(+) and HPV(-) patients were 17.57±8.73, 17.54±9.20 and 17.63±7.83, respectively. In the study group 10.2% of the patients and in the control group 8.5% had adequate vitamin D levels. No significant differences in vitamin D levels and in terms of distribution according to categorical vitamin D level have been observed between the groups (p=0.774, p=0.989). Conclusion: Vitamin D levels were comparable between HPV positive and HPV negative groups, but study and controls both had very low sufficient vitamin D levels.  In Turkey and especially in our region (Zonguldak), vitamin D deficiency is almost endemic, and this might be the main reason that both of the groups have very similar vitamin D measurements.